Treating ICB-resistant cancer by inhibiting PD-L1 via DHHC3 degradation induced by cell penetrating peptide-induced chimera conjugates - Yu-Ying Shi; Gang Fan; Ruirong Tan; Shan Li; Hua-Bing Sun; Rui Li; Mengni Yang; Shanshan Gao; Miao Liu; Meng-Yuan Dai (Cell Death and Disease)
Abstract The current selection of ligands for both proteins of interest (POI) and E3 ubiquitin ligase significantly restricts the scope of targeted protein degradation (TPD) technologies. This study introduces cell-penetrating peptide-induced chimera conjugates (cp-PCCs) targeting the DHHC3 enzyme involved in PD-L1 palmitoylation. This approach disrupts PD-L1’s immunosuppressive function, enhancing anti-tumor immunity. We developed cp-PCCs to degrade DHHC3, directly linking DHHC3-mediated PD-L1 palmitoylation to PD-L1 stability on tumor cells. Our research utilized both in vitro assays and in vivo experiments in immune checkpoint blockade-resistant mouse models. We focused on a CRBN-based cp-PCC named PCC16, which demonstrated a DC50 of 102 nmol for DHHC3 degradation and significantly reduced PD-L1 levels. In resistant models, PCC16 not only robustly downregulated PD-L1 but also exhibited substantial anti-tumor activity in vivo without significant toxicity. This outperformed traditional inhibitors, showcasing the potential of cp-PCC technology to bypass current PROTAC limitations. Our findings suggest that cp-PCCs offer a promising method for targeting PD-L1 through DHHC3 inhibition and support their continued exploration as a versatile tool in cancer immunotherapy, especially for tumors resistant to standard treatments.